Faisceaux imaginaires et cool medias : This Will Not Be Televised de Nicole Lizée - McKinley, Maxime (Circuit : musiques contemporaines, 2013)
The imagination of composer Nicole Lizée brings together disparate elements, largely drawn from cinema, philosophy, visual arts, and so-called popular music, with a pronounced penchant for the period from 1960-1980 and the ghostly effect thus conveyed. This article illustrates Lizée’s creative process through one of her characteristic works, This Will Not Be Televised (2005-2007), scored for DJ and seven instruments. Our analysis illustrates how the composer’s “beams of imagination” take form through a unique musical language, based here on a meticulously notated DJ part and extended through the instrumental ensemble, and which draws on cultural references, repetitive effects, and montages of juxtapositions and superpositions, and whose continuous form achieves cohesion through the use of repeats. In this way, the composer focuses on the connections that are generated in the memory and subjectivity of the hearer – the tabula rasa characteristic of McLuhan’s “cool” media.
Keywords: Nicole Lizée; This Will Not Be Televised; analyse; analysis; cool medias; tables tournantes; turntable; “cool” media

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)